Scaling of digital extension tools (PlantVillage NURU app) for diagnosis of cassava pests and diseases - Wosula, E.; Mbilinyi, N.; Issa, K.; Shirima, R.; Legg, J. (International Institute of Tropical Agriculture, 2024)
Cassava is the most important RTB crop in Africa, and its production and consumption are projected to increase due to its adaptability to climate change. Currently cassava is threatened by two viral diseases, cassava mosaic (CMD) and cassava brown streak (CBSD) disease. The aim of this project is scaling out the use of digital tool (PlantVillage NURU application) for diagnosis of pests and diseases in cassava. A total of 30 agricultural extension officers from Tanzania and Zambia were supplied with smart phones and trained in use of PlantVillage app to diagnose CMD, CBSD and cassava green mite (CGM). Analysis of data collected by research experts and extension officers show that the Plant Village app and extension officers have high misdiagnosis rates for CGM. Further improvements on the app model are proposed and routine expanded training of extension officers and lead farmers in use of digital tools for diagnosis of pests and diseases.